The Influence Of Competence, Compensation, and Organizational Climate on Employee Performance PT Persada Multi Mandiri Jakarta - Eric Hernawan (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
This study was conducted to determine directly the effect of three independent variables competence, compensation and organizational atmosphere on the performance of employees of PT. Persada Multi Mandiri Jakarta. Determination of employee performance is determined because the development of information technology is very fast causing very big changes in the world of business communication. Therefore, companies engaged in communication must prioritize appropriate human resource activities. On this occasion, three independent variables of competence, compensation and organizational atmosphere are used which have a direct effect either partially or simultaneously on the performance of the employees of Persada Multi Mandiri Jakarta. The method used in this research is a quantitative method with a descriptive research type that describes the phenomenon being studied through a regression equation that is determined after all research data is tested with validity, reliability, normality, multicollinearity and heteroscedasticity tests. The sample in this study was 100 respondents from a population of 132 people with an accuracy of 5%. The simple regression equation is said to be significant and positive if t count >t table . Meanwhile, for multiple regression equations, it will meet the significant and positive criteria if F count > F table . The results of the study found that all effects were positive and significant, because for the partial effect, all t count > t table (3,033; 4,789 and 4,692 > 2,365). Simultaneous effect is also significant and positive because F count >F table (10,182>3.99). The partial effect in percent (%) for compensation, competence, and organizational atmosphere was (8.6%; 19.0% and 18.3%). This effect is true because all F count >F table (9,197; 22,930 and 22,012 > 6.90) While the simultaneous effect in percent is 21.8 %). This effect is true because F count >F table (10,182>3.99).